Conscientization of social cryptomnesia reduces hostile sexism and rejection of feminists - Vernet, J.-P.; Vala, J.; Amâncio, L.; Butera, F. (Social Psychology, 2009)
This paper develops a hypothesis concerning the conscientization of social cryptomnesia, claiming that it is possible to reduce the rejection of minorities by reminding the population that a certain value has been promoted by a certain minority. Participants (N = 93) first reported their attitudes toward women’s rights and feminist movements. They were then confronted with their higher appreciation of women’s rights over feminists (social cryptomnesia) and blamed for it (conscientization) in a more versus less threatening manner. Results indicated that conscientization can be effective not only in inducing a more positive attitude toward feminists, but also in decreasing hostile sexism when the threat is lower. Implications for minority influence research are discussed.